2019
DOI: 10.1111/fcp.12507
|View full text |Cite
|
Sign up to set email alerts
|

Refining the therapeutic range of posaconazole and isavuconazole for efficient therapeutic drug monitoring using a bioassay approach

Abstract: Therapeutic drug monitoring (TDM) of antifungal triazole was recommended, except for isavuconazole (ISA) whose target trough concentrations (Cmin) need to be specified. Concerning posaconazole (POS), tablet formulation results in higher exposure but no upper Cmin threshold has been yet proposed. We aimed to investigate the pharmacokinetic–pharmacodynamic relationship of POS and ISA, using a bioassay approach as surrogate marker of antifungal activity, in order to refine the therapeutic Cmin of both antifungals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…However, other studies contradicted this conclusion and found a link between the level of antifungal exposure and the susceptibility of clinical Aspergillus fumigatus isolates [ 43 ] or clinical outcome [ 44 ]. A recent French study compared plasma trough concentrations of isavuconazole with the concentration found at the zone of fungal growth inhibition in order to specify the clinical therapeutic threshold [ 45 ]. A concentration of 2 mg/L conferred 52% of the maximum in vitro antifungal activity on Aspergillus fumigatus , similar to that observed with posaconazole at therapeutic dose.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies contradicted this conclusion and found a link between the level of antifungal exposure and the susceptibility of clinical Aspergillus fumigatus isolates [ 43 ] or clinical outcome [ 44 ]. A recent French study compared plasma trough concentrations of isavuconazole with the concentration found at the zone of fungal growth inhibition in order to specify the clinical therapeutic threshold [ 45 ]. A concentration of 2 mg/L conferred 52% of the maximum in vitro antifungal activity on Aspergillus fumigatus , similar to that observed with posaconazole at therapeutic dose.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate dose data for posaconazole suspension suggest that TDM is valuable for improving efficacy, assessing treatment failure due to suboptimal drug exposure and minimising possible azole‐induced toxicity 12 . Currently, the main methods for the determination of posaconazole blood concentrations are chromatography, mass spectrometry, bioassay and fluorescence assays 99–102 . Bioassays and fluorometric assays are less commonly used in clinical practice because of their low selectivity and susceptibility to ambient temperature, pH and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…12 Currently, the main methods for the determination of posaconazole blood concentrations are chromatography, mass spectrometry, bioassay and fluorescence assays. [99][100][101][102] Bioassays and fluorometric assays are less commonly used in clinical practice because of their low selectivity and susceptibility to ambient temperature, pH and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This method allows ISA quantification in plasma from 0.1 to 20 mg/L, with good precision (intra- and inter-day coefficient of variation <15%) and accuracy (intra and inter-day biases ± 15%). ISA Cmin are considered therapeutic in our institution if they are between 2 and 5 mg/L [ 9 , 19 ] and any dose adjustment was left to the discretion of the clinician.…”
Section: Methodsmentioning
confidence: 99%